1999
DOI: 10.1046/j.1460-9568.1999.00601.x
|View full text |Cite
|
Sign up to set email alerts
|

Amino‐terminal region of secreted form of amyloid precursor protein stimulates proliferation of neural stem cells

Abstract: Beta-amyloid precursor protein (APP) has been reported to be expressed in the CNS from the early stages of development. However, the functional role of APP during early development remains unclear. In the present study, we found that the secreted form of APP (sAPP) significantly enhanced proliferation of neural stem cells. Cells were prepared from 13-day embryonic rat neocortex, which was dissected with a Pasteur pipette to make cell clusters. After 12 h of cultivation in the medium without serum, cells around… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
1
2

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(85 citation statements)
references
References 40 publications
2
80
1
2
Order By: Relevance
“…Cultured keratinocytes also exhibit sAPP-binding sites similar to the ones we observed in the SVZ or on cultured NS. In line with the results presented here, sAPP was described to stimulate proliferation of embryonic neural stem cells (Hayashi et al, 1994;Ohsawa et al, 1999). Accordingly, we could detect sAPP-binding sites not only on adult NS cells and SVZ but also on NS cells cultured from the embryonic brain (Fig.…”
Section: Specificity Of Sapp Binding and Activitysupporting
confidence: 90%
See 2 more Smart Citations
“…Cultured keratinocytes also exhibit sAPP-binding sites similar to the ones we observed in the SVZ or on cultured NS. In line with the results presented here, sAPP was described to stimulate proliferation of embryonic neural stem cells (Hayashi et al, 1994;Ohsawa et al, 1999). Accordingly, we could detect sAPP-binding sites not only on adult NS cells and SVZ but also on NS cells cultured from the embryonic brain (Fig.…”
Section: Specificity Of Sapp Binding and Activitysupporting
confidence: 90%
“…A function for sAPP in regulating the proliferation of different cell types has been proposed in previous studies performed on cell lines (Hayashi et al, 1994;Hoffmann et al, 2000;Ohsawa et al, 1999;Pietrzik et al, 1998;Saitoh et al, 1989). Interestingly, sAPP has been described as an autocrine regulator of epidermal basal cell proliferation (Hoffmann et al, 2000), which, similar to SVZ progenitor proliferation, is under the control of TGFα, a member of the EGF family that acts though the EGF receptor.…”
Section: Specificity Of Sapp Binding and Activitymentioning
confidence: 89%
See 1 more Smart Citation
“…sAPP has been suggested to exhibit neurotrophic, synaptogenic, and growth-promoting properties (Jin et al, 1994;Ohsawa et al, 1999;Rossjohn et al, 1999), and AICD has been reported to function in transcriptional regulation (Cao and Sudhof, 2001). A potential role of presenilin-dependent APP processing and signaling cannot be tested directly because of the early lethal phenotype of PS1/PS2 double null embryos (Donoviel et al, 1999;Herreman et al, 1999) and a large number of potential PS processing substrates reported (for review, see De Strooper, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Neuroblastoma SH-SY5Y cells were cultured in DMEM (Invitrogen) with 15% FBS and 20 units͞ml penicillin-20 g͞ml streptomycin. Primary cultures of neocortical neurons were prepared from 18-day rat embryos as described (19,20) with slight modifications. In brief, neocortical tissues were cleaned of meninges, minced, and treated with 0.25% trypsin and 0.01% DNase I.…”
Section: Construction and Preparation Of Ptd-fnk Ptd-bcl-xl And Ptdmentioning
confidence: 99%